Influence of ultrasound treatment on meat quality and microstructure of semitendinosus muscle from old Philippine carabaos (Bubalus bubalis) - Go, Francene P.; Dumelod, Benelyn D.; Abanto, Oliver D. (Quezon City University of the Philippines Diliman, 2020)
Commercially available carabeef (CB) have tough texture as most are sourced from old, retired carabaos. This research explored the feasibility of ultrasound technology in improving the tough texture associated with CB. This benefits the local industry and enables end-consumers to gain better access to nutritious, high quality, and affordable meat. Semitendinosus muscles from Philippine carabaos were exposed to US generated using a water-bath type sonicator then analyzed for changes in meat quality. The effects of treatment duration (TD: 20, 30, 40 min) and water bath temperature (WBT: 5, 12, 25°C) on CB tenderness (T), pH, moisture content (MC), water-holding capacity (WHC), and color were investigated. Across TD, results indicated general improvement in T with some significant effects observed; color results showed an increase in lightness (L*) and yellowness (b*) (p >0.05), but no change in redness (a*); pH, MC, and WHC were not significantly affected by TD (p<0.05). Across WBT, significant effects with no conclusive trends were found for pH, T, and color (L*, a*, b*) (p<0.05), while no effects were found for MC and WHC (p>0.05). Changes in microstructure analyzed using scanning electron microscopy SEM showed that US exposure damaged connective tissue layers in CB. This resulted in loss of integrity, cavities, and disorganized microstructure which translated to improved tenderness. This study showed the potential of US technology in improving CB tenderness with minimal effects on meat quality. Results of this research can be applied in future optimization studies that cover industrial applications, process conditions and animal characteristics.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Food processing; Food -- quality; Meat -- quality; Carabao meat